Influence of the kitchen in the home - Yenawine, Ora Gertrude (My University, 1895)
Introduction: Many of us do not know how much our kitchens ought to mean to us and the consequence is they are often neglected. Our grandmothers loved and honored their kitchens and why should not we? Perhaps one reason for this was that in their day the house work was about the only occupation for women, but in this day and age woman is constantly taking up different occupations in life and thus comes the neglect of the kitchen. It may be said that there is a difference between our country kitchens and our city kitchens, both may be clean and neat but one is more inclined to think of the country kitchen as being more home like, perhaps too the one contains more good wholesome fruits and vegetables than the other, which is more likely to contain a larger proportion of sweets. Every one or nearly every one loves the old fireplaces much more than the ranges of today. The country kitchen contains nothing so elaborate as the city kitchen is liable to contain, and taking into consideration every thing, perhaps in the long run the country kitchen is more beautiful to the tired eye than the other, and one feels rested on entering it.
Citation: Yenawine, Ora Gertrude. Influence of the kitchen in the home. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Domestic science; Kitchen; Theses; Manuscripts (documents)